Uncertainty and Risk in Financial Markets: A Global Bibliometric Study - Judijanto, Loso (Westscience Press, 2025)
Uncertainty and risk are enduring concerns in the study and practice of financial markets, especially in light of recent global disruptions such as geopolitical tensions, the COVID-19 pandemic, and climate-related events. This study conducts a comprehensive bibliometric analysis to map the intellectual structure, thematic evolution, author collaboration networks, and global research distribution in the domain of financial market uncertainty and risk. Using data from the Scopus database spanning 2000–2025, and employing VOSviewer for visualization, we identify key research clusters—ranging from risk assessment and stochastic modeling to emerging topics such as geopolitical risk and climate uncertainty. Overlay and heatmap visualizations reveal a temporal shift from traditional quantitative finance to interdisciplinary approaches integrating economic, environmental, and policy-driven risks. Co-authorship and country collaboration analyses highlight the pivotal roles of the United States, China, and Europe in shaping the global discourse, alongside growing contributions from emerging economies. The findings suggest that financial risk research is becoming increasingly global, data-driven, and responsive to systemic challenges, offering valuable insights for scholars, policymakers, and practitioners navigating the complexities of modern financial systems.